879Sleep Duration and all-cause and cause-specific mortality in people with diabetes. (2nd September 2021) - Melaku, Yohannes Adama; Appleton, Sarah; Reynolds, Amy; Gills, Tiffany; Adams, Robert
Abstract: Background: Evidence shows that habitual short and long sleep is associated with higher mortality risk in the general population. However, studies on the association between sleep duration and mortality in people with diabetes are scarce. Methods: Data from the National Health Interview Survey (NHIS) of the United States (US) between 2004 and 2014 (N = 32, 766) were used. Self-reported habitual sleep duration for those with self-reported doctor diagnosed diabetes was categorized as ≤ 6 hr (short sleep), 7-8 hr (adequate sleep), and ≥9 hr (long sleep). Mortality status and cause of death data were retrieved from the US National Death Index and linked. We used adjusted Cox proportional models to examine the association between sleep duration and mortality risk. Dose-response relationships were quantified. Sensitivity analysis was performed excluding cardiovascular and cancer cases. Results: In the median follow-up time of 4.6 years (171, 375.2 person-years), 5312 all-cause, 1129 cardiovascular, 1148 cancer and 494 diabetes deaths were recorded. Whereas short sleep duration (adjusted hazard ratio (aHR)=1.04; 95% confidence interval (CI): 0.97, 1.11) in diabetic patients was not associated with all-cause mortality, long sleep duration was positively (aHR=1.43; 95% CI: 1.30, 1.57) associated with increased mortality risk. A similar trend of association was found with cause-specific mortality and the dose-response analysis identified a "J" shape association. Similar results were found upon sensitivity analysis. Conclusions: Long but not short sleep duration is associated with all-cause and cause-specific mortality in diabetic patients. Key messages: Sleep should be part of behavioural intervention to prevent premature mortality in those with diabetics.